Evaluation of hypothermia on the in vitro metabolism and binding and in vivo disposition of midazolam in rats. (15th July 2015) - Miyamoto, Hirotaka; Matsueda, Satoshi; Moritsuka, Akihiro; Shimokawa, Kenta; Hirata, Haruna; Nakashima, Mikiro; Sasaki, Hitoshi; Fumoto, Shintaro; Nishida, Koyo
Abstract The effect of hypothermia on the in vivo pharmacokinetics of midazolam was evaluated, with a focus on altered metabolism in the liver and binding to serum proteins. Rat primary hepatocytes were incubated with midazolam (which is metabolized mainly by CYP3A2) at 37, 32 or 28 °C. The Michaelis–Menten constant (Km) and maximum velocity (Vmax) of midazolam were estimated using the Michaelis–Menten equation. The Km of CYP3A2 midazolam remained unchanged, but the Vmax decreased at 28 °C. In rats, whose temperature was maintained at 37, 32 or 28 °C by a heat lamp or ice pack, the plasma concentrations of midazolam were higher, whereas those in the brain and liver were unchanged at 28 °C. The tissue/plasma concentration ratios were, however, increased significantly. The unbound fraction of midazolam in serum at 28 °C was half that at 37 °C. These pharmacokinetic changes associated with hypothermic conditions were due to reductions in CYP3A2 activity and protein binding. Copyright © 2015 John Wiley & Sons, Ltd.